A review on laws and regulations: misrepresentation of facts using legitimate sales brochure by life insurance agent / Nur Alia Atika Siswandy and Dira Aisha Amran - Siswandy, Nur Alia Atika; Amran, Dira Aisha (Faculty of Law, 2016)
This study is carried out to identify the misrepresentation done by the life insurance agents in Malaysia and whether the laws in Malaysia are adequate enough to protect the rights of insured who bought life insurance policy especially the one with the investment-linked products. Other than that, it is also to identify whether there is any country has Misrepresentation Act that govern the rights of insured to be as a reference to the Malaysian laws and do our laws need to be changed in regards to the insured’s right. Few interviews conducted with Prudential’s life insurance agents. Cases from United States in regards to misrepresentation had been reviewed and were used to support the information. The data showed that existing law does not comprehensive enough to protect Malaysian life insurance insured on their rights in term of misrepresentation act by the agents. This is because each of the Acts has its own limitations and terms that have been covered. Furthermore, it is hardly to tell whether the agent had breached their duty to the insured in giving genuine information before they buy the life insurance policy with investment-linked. In fact, in term of the enforcement of the law is weak. Hence, authority is recommended to have specific Act that could protect the insured and improvise the protection.